Cu(II), Co(II), Mn(II) complexes with 5-phenyltetrazole and polypyridyl ligands: Synthesis, characterization and evaluation of the cytotoxicity and antimicrobial activity. (15th September 2021) - Eremina, Julia A.; Ermakova, Ekaterina A.; Smirnova, Ksenia S.; Klyushova, Lyubov S.; Berezin, Alexey S.; Sukhikh, Taisiya S.; Zubenko, Alexander A.; Fetisov, Leonid N.; Kononenko, Kristina N.; Lider, Elizaveta V.
Graphical abstract: Reaction of Cu(II), Co(II), and Mn(II) salts with 5-phenyltetrazole (HL) and polypyridine ligands produced the coordination compounds of the various composition, several crystal structures were determined. The cytotoxic properties of the complexes have been investigated in vitro on Hep-2, HepG2, and MCF-7 cell lines and compounds [Cu2 (dmphen)2 (L)4 ], [Cu(phendione)(L)2 ] are found to be the most cytotoxic. The antimicrobial activity of complexes and ligands has been investigated against Escherichia coli, Staphylococcus aureus, Penicillium italicum and Colpoda steinii . Abstract: In this work, six new mixed-ligand Cu(II), Co(II), Mn(II) complexes with 5-phenyltetrazole (HL) and polypyridine ligands (phen – 1, 10-phenanthroline, dmbipy – 2, 2′-bi-4-picoline, dmphen – 4, 7-dimethyl-1, 10-phenanthroline, phendione – 1, 10-phenanthroline-5, 6-dione), namely, [Cu(dmbipy)(L)2 ] (1 ), [Cu2 (dmphen)2 (L)4 ] (2 ), [Cu(phendione)(L)2 ] (3 ), [Co3 (phen)2 (L)6 ] (4 ), [Mn3 (phen)2 (L)4 (OAc)2 ] (5 ), [Mn(H2 O)4 (phen)]·phen·2L (6), are reported. Complexes have been characterized by EPR and IR-spectroscopy, elemental, thermogravimetric and powder X-ray diffraction analysis. Molecular structures of [Cu(dmphen)2 L]·L·6H2 O (2a ), [Co3 (phen)2 (HL)2 (L)4 (OH)2 ]·1.9EtOH·1.1DMSO (4a ), [Mn3 (phen)2 (L)4 (OAc)2 ]·H2 O (5 ·H2 O ) and [Mn(H2 O)4 (phen)]·phen·2L (6 ) have been determined by single crystal X–ray diffraction. The UV–vis spectroscopy has been applied to study the behavior of the compounds in solution. All complexes have been screened in vitro for their cytotoxic activity against human cancer cell lines: larynx carcinoma (Hep2), hepatocellular carcinoma (HepG2) and breast adenocarcinoma (MCF-7). Cu(II) complexes exhibit significant dose-dependent cytotoxic effect: [Cu2 (dmphen)2 (L)4 ] (2 ), [Cu(phendione)(L)2 ] (3 ) are found to be the most cytotoxic. The antimicrobial activity of complexes and ligands has been investigated against Escherichia coli, Staphylococcus aureus, Penicillium italicum and Colpoda steinii .